(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The paper deals with the chemical composition of coloured glaze of 16 tiles from restored furnace of Biržai castle. It demonstrates that glaze is enriched with different elements compared to soil and therefore can be one of the multiple contamination sources of soil, especially in the old urban quarters. High variability of element contents in glaze is predetermined by its colour. However, Bi, Sb, Ag, Pb, Sn, Cu are elements-indicators of coloured glaze chemical composition. 1 g of coloured glaze added to 1 kg of soil causes at least medium level of local contamination.